2020
DOI: 10.12688/hrbopenres.13055.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effect of cognitive impairment on the risk of admission to long-term care after stroke

Abstract: Introduction: Admission to long-term care (LTC) post-stroke can be a significant source of costs. Studies evaluating the effect of cognitive impairment (CI) and dementia on risk of LTC admission post-stroke have not been systematically reviewed. The aim of this paper was to conduct a systematic review and meta-analysis of studies of the association between post-stroke CI/dementia and admission to LTC. Patients and methods: PubMed, PsycInfo and Cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…While stroke and poor cognitive function were associated with increased emergency services utilisation in the unadjusted models, disability and depression appeared to mediate emergency visits in the adjusted analysis. Stroke survivors and individuals with cognitive impairment are commonly affected by disability and depression [ 15 , 19 , 49 ], which may explain why no significant association was found once these confounders were included in the model. The number of nights spent in hospital also failed to reach significance in the adjusted regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While stroke and poor cognitive function were associated with increased emergency services utilisation in the unadjusted models, disability and depression appeared to mediate emergency visits in the adjusted analysis. Stroke survivors and individuals with cognitive impairment are commonly affected by disability and depression [ 15 , 19 , 49 ], which may explain why no significant association was found once these confounders were included in the model. The number of nights spent in hospital also failed to reach significance in the adjusted regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…PSCI is associated with impaired activities of daily living (ADL), which in turn may result in greater utilisation of healthcare services and reduced capacity for independent living [ 17 ]. Individuals with PSCI are more likely to be re-admitted to hospital [ 18 ] and a recent systematic review found a significant two-fold increase in long-term care admissions of patients with PSCI and dementia [ 19 ]. The exact trajectory of PSCI is unpredictable—some stroke survivors show improvement or stable cognitive function over time, while others experience cognitive decline [ 9 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal research has focused on the specific effects of post-stroke cognitive status on functional outcomes (such as functional gains, rehabilitation stays, and discharge living settings) following inpatient rehabilitation. A few previous studies have suggested that impaired cognition correlates with older age [8], longer rehabilitation stays [2] [6], and discharge to extended care facilities [2] [9] [10] [11] [12]. A single study reported a decrease in functional gains among cognitively impaired patients [13], but other studies demonstrated improvements in motor function among stroke patients with impaired cognition [6] [14].…”
Section: Introductionmentioning
confidence: 99%
“…While the risk of nursing home entry for those with PSCI has been examined, results have varied by study setting, sample size and follow–up periods. Consequently, the strength of the effect of PSCI on nursing home placement has varied between studies [ 16 ]. The characteristics of stroke survivors admitted to nursing homes have been examined in a number of studies [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%